Fungi: A Neglected Candidate for the Application of Self-Healing Concrete - Jin, Congrui; Yu, Rui; Shui, Zhonghe (Frontiers in Built Environment, 2018)
Self-healing mechanism in concrete has been so far achieved mainly by three approaches: autogenous healing, encapsulation of polymeric material, and biologically induced mineralization of calcium carbonate. The microbial approach prevails over the other two approaches due to the high compatibility between the filler material and the concrete compositions. Although the term “microbe” refers to many different types of organisms, research work on self-healing concrete has been so far restricted to bacteria. In this perspective article, we review the current status of bacteria-mediated self-healing concrete and summarize the prospects for future advances. In particular, we point out that fungi may have distinctive advantages over other microbes to be used as self-healing agents.